2008
DOI: 10.1038/sj.bjc.6604241
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies after breast cancer: the impact of different treatment modalities

Abstract: Treatment for non-metastatic breast cancer (BC) may be the cause of second malignancies in long-term survivors. Our aim was to investigate whether survivors present a higher risk of malignancy than the general population according to treatment received. We analysed data for 16 705 BC survivors treated at the Curie Institute (1981 -1997) by either chemotherapy (various regimens), radiotherapy (high-energy photons from a 60 Co unit or linear accelerator) and/or hormone therapy (2 -5 years of tamoxifen). We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 53 publications
7
67
1
1
Order By: Relevance
“…We and other authors demonstrated that the recurrence rate in BRCA1/BRCA2 carriers is not increased in this population of patients [28][29][30][31][32]. On the contrary, it is well known that after long latent period, the radiation therapy for breast cancer can induce malignant tumours after a latency of several years [33,34]. The risk of second cancers in this population of patients is insufficiently documented [35,36].…”
Section: Introductionmentioning
confidence: 82%
“…We and other authors demonstrated that the recurrence rate in BRCA1/BRCA2 carriers is not increased in this population of patients [28][29][30][31][32]. On the contrary, it is well known that after long latent period, the radiation therapy for breast cancer can induce malignant tumours after a latency of several years [33,34]. The risk of second cancers in this population of patients is insufficiently documented [35,36].…”
Section: Introductionmentioning
confidence: 82%
“…These findings have been attributed to shared lifestyle and genetic risk factors, carcinogenic effect of treatment (in particular radiotherapy), and most commonly to better medical surveillance of women with previous breast cancer. Most of those studies addressing melanoma risk after breast cancer concerned patients treated in the distant past and therefore with treatment regimens not including hormonal therapy (15,16), or lacked antiestrogen data or when available, did not evaluate if hormonal therapy influenced melanoma risk (17,19,(20)(21)(22)24). To our knowledge, only 2 prior studies evaluated melanoma cancer risk among breast cancer patients according to hormonal therapy (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Le cancer thyroïdien (CT) peut être associé à des cancers primitifs de nombreux organes différents, notamment le cancer du sein [20][21][22], les hémopathies malignes [23], le cancer de l'oesophage [24], les cancers de la tête et du cou [25], le cancer du rein, de la prostate, de l'ovaire [26], les cancers du cerveau, du système nerveux central [27] et le cancer colorectal.…”
Section: Discussionunclassified